Between Custom and Justice: Contemporary Muamalah Review of the Weighing System in Palm Oil Transactions in Silaut District - Neswati Neswati; Jonri Jonri (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
This research aims to analyze the weighing system used in the sale and purchase of palm oil plantation products in Silaut District through the perspective of contemporary muamalah jurisprudence. The primary objective is to determine whether the 5-kilogram deduction applied per weighing aligns with the principles of Sharia economic law, particularly justice and mutual consent. This study employed a qualitative field research method, with data collected through interviews involving two palm oil bosses, two farmers, and two loose-fruit collectors selected using purposive sampling. Data analysis followed the Miles and Huberman framework, consisting of data reduction, data display, and conclusion drawing. The results show that the 5-kilogram deduction system has been consistently practiced since 2003 and is accepted by all parties because it reflects the estimated weight of the iron base attached to the scale. The findings indicate that this system does not constitute fraudulent weighing as prohibited in Surah Al-Muthaffifin; instead, it operates as an authentic ‘urf upheld by community consensus. The study concludes that the deduction system complies with contemporary Sharia principles of justice and willingness, and it positively influences trust and transactional stability among local palm oil traders.